Faktor-faktor yang berhubungan dengan perilaku seks bebas pada anak buah kapal (ABK) - Aspawi, Asril; Djamaluddin, Abikusno; Rukmana, Nova Mega (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Casual sex is a major risk factor for the transmission of sexually transmitted diseases (STDs), including HIV/AIDS, especially among migrant workers such as crew members (ABK). HIV/AIDS cases in Indonesia are also showing an increasing trend. Purpose: This study aims to determine the relationship between knowledge, attitudes, social support, and the work environment with casual sex. Method: This quantitative study used a cross-sectional approach and a sample of 68 crew members. The study was conducted among crew members at Bakauheni Port, within the working area of ​​the Class I Panjang Health Quarantine Center in 2025. Data were analyzed using univariate and bivariate analyses using the Chi-Square test. Results: The Chi-Square test showed that knowledge (p=0.002; OR=2) and attitudes (p=0.019; OR=2.35) were significantly associated with casual sex. Social support (p=0.366; OR=0.81) and the work environment (p=0.861; OR=0.92) were not significantly associated. Conclusion: Improving education, such as implementing peer education and displaying posters about the dangers of promiscuous sexual behavior on ships, is crucial in preventing promiscuous sexual behavior among seafarers.   Keywords: Attitude; Seafarers; Environment; Knowledge; Promiscuous Sexual Behavior; Social Support; Work.   Pendahuluan: Perilaku seks bebas merupakan salah satu faktor risiko utama dalam penularan penyakit menular seksual (PMS) termasuk HIV/AIDS, terutama pada kelompok pekerja migran seperti Anak Buah Kapal (ABK). Kasus HIV/AIDS di Indonesia juga menunjukkan tren peningkatan. Tujua: Penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan, sikap, dukungan sosial, dan lingkungan kerja dengan perilaku seks bebas. Metode: Penelitian kuantitatif dengan pendekatan cross sectional dan sampel sebanyak 68 ABK. Penelitian dilakukan pada ABK di Pelabuhan Bakauheni, wilayah kerja Balai Kekarantinaan Kesehatan Kelas I Panjang Tahun 2025. Analisis data menggunakan analisis univariat dan bivariat menggunakan uji Chi-Square. Hasil: Uji Chi-Square menunjukkan bahwa pengetahuan (p=0,002; OR=2) dan sikap (p=0,019; OR=2,35) berhubungan signifikan dengan perilaku seks bebas. Sedangkan dukungan sosial (p=0,366; OR=0,81) dan lingkungan kerja (p=0,861; OR=0,92) tidak berhubungan. Simpulan: Peningkatan edukasi seperti penerapan peer education dan pemasangan poster tentang bahaya perilaku seks bebas di kapal sangat penting dalam pencegahan perilaku seks bebas pada ABK.   Kata Kunci: ABK; Dukungan Sosial; Lingkungan; Pengetahuan; Perilaku Seks Bebas; Sikap; Kerja.